SELF DISCLOSURE KALANGAN GAY KEPADA KELUARGA DI PROVINSI BALI - Kusuma Yanti, Ni Made Wiwin; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2019)
ABSTRACT Indonesia is one of many countries in the world that deny any sexual preference other than heterosexual because gay and bisexsual are considered wrong in term of religion and norm. From research that have been done by PEW Research Center in 2007 said that only 3% of the respondence from Indonesia support gay couple and the other 97% said didnt. This thing makes gay people choose the way of closeted community and extremely hard to surface. This thing also make gay people are deciding to stay away from their family and friends. This research focused on the self disclosure on gay in Bali Province. This research using qualitative method and social penetration. The object is gay that already open to their family. The result is most of the gay people are usualy cover them selves because they are aware that other people can not accept them by who they are.   Keywords: Family, Gay,Self Disclosure, Social Penetration